Pengaruh Karakteristik Usia dan Gender Santri di Ma’had Bakkah Martapura terhadap Kesadaran Pemilahan Sampah Organik dan Anorganik - Hesti Wijayanti; Primata Mardina; Rinna Juwita; Lailan Ni'mah; Jefriadi Jefriadi; Desi Nurandini; Indah Retno Wulandary; Yulia Nurul Ma'rifah (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2026)
Children's awareness of disposing of waste in designated bins is a crucial factor in environmental health education, fostering a clean and healthy environment. A lack of understanding among children regarding waste management can be addressed through educational approaches that provide knowledge about organic and inorganic waste types. These efforts should begin early, during the formative "golden age" of behavioral development, as habits formed at this stage are easier to establish and yield more visible results in later life. Developing waste management behaviors at an early age can start with cultivating the habit of sorting and disposing of waste properly, which is expected to become a lifelong practice.The target group for this community service activity consisted of first, second, and third-grade students of SDITQ Ma’had Bakkah, Martapura. The objective of this community service initiative was to educate students who still disposed of waste carelessly, raise awareness about the importance of separating organic and inorganic waste, and implement waste sorting practices within the Ma’had Bakkah environment. The outcomes of this initiative included students gaining an understanding of the importance of maintaining cleanliness both at school and beyond, as well as learning to manage and sort organic and inorganic waste. Furthermore, the activity successfully fostered behavioral changes among the community, encouraging greater awareness and commitment to waste management and sorting within the school environment. Keywords: awareness; organic waste; inorganic waste; students (santri); Ma’had Bakkah